1998
DOI: 10.1191/096120398678920343
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic-pituitary-adrenal axis function and prolactin secretion in systemic lupus erythematosus

Abstract: The objective was to study the response of cortisol and of prolactin (PRL) to specific stimuli in systemic lupus erythematosus (SLE). We measured the response of cortisol to insulin-induced hypoglycemia and of PRL to thyrotropin releasing hormone (TRH) in seven patients with active untreated SLE and in ten paired control subjects. All were women with regular menstrual cycles. With the exception of two patients, they had never received corticosteroids before the study. The basal serum levels of cortisol (12.5+/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 16 publications
(10 reference statements)
1
42
0
2
Order By: Relevance
“…25 A blunted HPA axis has been associated with susceptibility to autoimmune and inflammatory disease in chickens (a model for autoimmune thyroiditis), 143 certain mouse lupus models, 144,145 and in the inbred rat strains 146,147 ( Table 1). The association between blunted HPA axis and autoimmune, inflammatory and allergic diseases has been reported in human illness including RA, [148][149][150][151][152][153] Sjogren's syndrome, 154 systemic lupus erythematosus, 155 multiple sclerosis, 156,157 allergic asthma and atopic skin disease. [158][159][160] (Table 1).…”
Section: Neuroendocrine Dysregulations In Autoimmune Diseasesmentioning
confidence: 99%
“…25 A blunted HPA axis has been associated with susceptibility to autoimmune and inflammatory disease in chickens (a model for autoimmune thyroiditis), 143 certain mouse lupus models, 144,145 and in the inbred rat strains 146,147 ( Table 1). The association between blunted HPA axis and autoimmune, inflammatory and allergic diseases has been reported in human illness including RA, [148][149][150][151][152][153] Sjogren's syndrome, 154 systemic lupus erythematosus, 155 multiple sclerosis, 156,157 allergic asthma and atopic skin disease. [158][159][160] (Table 1).…”
Section: Neuroendocrine Dysregulations In Autoimmune Diseasesmentioning
confidence: 99%
“…Estradiol stimulates prolactin secretion, and prolactin suppresses gonadal steroid synthesis (69,70). As shown in Table 4 and Figure 4, several studies have examined the relationship of prolactin and SLE in adults, comparing either the mean concentrations in patients with those of controls or normal and abnormal prolactin concentrations (hyperprolactinemia), with or without a control population (71)(72)(73)(74)(75)(76)(77)(78)(79)(80)(81)(82)(83)(84)(85)(86)(87). Seven of 10 female-only and 2 of 4 male-only SLE studies showed significantly increased serum prolactin concentrations in adult lupus patients compared with controls.…”
Section: Serum Prolactinmentioning
confidence: 99%
“…Other possibilities include cytokine-stimulated pituitary prolactin release (54,55), production of immunoreactive prolactin peripherally (98,99), or aberrant pituitary prolactin secretion in lupus patients (74,75). Some of these explanations are, however, superficially not compatible with the other steroid hormone abnormalities seen in female SLE patients.…”
Section: Serum Prolactinmentioning
confidence: 99%
“…The association between a blunted HPA axis and autoimmune, inflammatory and allergic diseases is also relevant to humans with illnesses including rheumatoid arthritis (Neeck et al 1990, Cash et al 1992, Chikanza et al 1992, Cutolo et al 1999, Gutierrez et al 1999, systemic lupus erythematosus (Gutierrez et al 1998), Sjogren's syndrome (Johnson et al 1998), allergic asthma and atopic skin disease (Buske- Kirschbaum et al 1997), fibromyalgia (Crofford et al 1994 and chronic fatigue syndrome (Demitrack et al 1991). However, it may not be necessary for the HPA axis defect to occur centrally, at the level of the hypothalamus or pituitary, to predispose to enhanced susceptibility to autoimmune/inflammatory disease.…”
Section: Effects Of Blunted Hpa Axis Responses On Immune Function Andmentioning
confidence: 99%